2022
DOI: 10.1002/advs.202201271
|View full text |Cite
|
Sign up to set email alerts
|

An Injectable Epigenetic Autophagic Modulatory Hydrogel for Boosting Umbilical Cord Blood NK Cell Therapy Prevents Postsurgical Relapse of Triple‐Negative Breast Cancer

Abstract: Triple‐negative breast cancer (TNBC) exhibits resistance to conventional treatments due to the presence of cancer stem cells (CSCs), causing postsurgical relapse and a dismal prognosis. Umbilical cord blood natural killer (UCB‐NK) cell‐based immunotherapy represents a promising strategy for cancer treatment. However, its therapeutic efficacy is greatly restrained by downregulation of the NK cell activation ligand MHC class I‐related chain A/B (MICA/B) and autophagy‐mediated degradation of NK cell‐derived granz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…NK cells, as innate lymphocytes, are crucial in immune surveillance against cancer, particularly in preventing metastases due to their ability to recognize and kill cancer cells ( 40 42 ). It has been revealed that sorafenib can enhance NK cell antitumor immunity in HCC, which closely correlates with its therapeutic efficacy ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…NK cells, as innate lymphocytes, are crucial in immune surveillance against cancer, particularly in preventing metastases due to their ability to recognize and kill cancer cells ( 40 42 ). It has been revealed that sorafenib can enhance NK cell antitumor immunity in HCC, which closely correlates with its therapeutic efficacy ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…137 In Gong et al 's report, the encapsulated mesoporous bioactive glass nanoparticles can generate abundant silanol groups at their external surface in aqueous solution. 138 These silanol groups interacted with amino groups to strengthen the crosslinking formed by Schiff's base bonds in the hydrogel. In addition, various stimuli-responsive injectable hydrogels have been developed.…”
Section: Formulations Of Hydrogels For Postoperative Tumor Therapymentioning
confidence: 99%
“…A pH-responsive injectable hydrogel formed by the crosslinking of Schiff's base bonds was reported to co-deliver 3-methyl adenine and suberoylanilide hydroxamic acid (SAHA) to treat triple-negative breast cancer (TNBC). 138 When this hydrogel was injected into the surgical resection site, it could transform into a steady hydrogel in situ and achieve a pH-responsive continuous drug release to hinder the recurrence of TNBC after resection. In another study, Liu et al introduced UCNPs to construct an injectable and near-infrared (NIR)-light-responsive hydrogel with electrostatic interactions between UCNPs-Au and DNA (Fig.…”
Section: Formulations Of Hydrogels For Postoperative Tumor Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…One significant advantage of hydrogels is their tunable mechanical properties. 57 Through the regulation of polymer composition, crosslinking density, and formulation parameters, it is possible to customize the mechanical properties of hydrogels to align with the particular demands of the target tissue or application. This adaptability empowers hydrogels to replicate the mechanical attributes of natural tissues, promoting their integration and providing the necessary scaffolding for cellular growth and tissue regeneration.…”
Section: Hydrogelsmentioning
confidence: 99%